An iterative design of ubiquitous learning modules for enhancing digital pedagogy in the Sekolah Penggerak - Pratama Benny Herlandy; Wandi Syahfutra (Universitas Muhammadiyah Malang, 2025)
This study addresses the urgent need for adaptive digital learning innovations in schools undergoing systemic reform, particularly within the Sekolah Penggerak program in Indonesia. These schools face significant challenges in sustaining instructional continuity due to demanding teacher development agendas and limited digital infrastructure. The research aims to design, implement, and validate ubiquitous learning (u-learning) modules that enhance digital pedagogy while aligning with real-world classroom dynamics. Employing a Design-Based Research (DBR) methodology, the study was conducted through iterative cycles of design, testing, feedback, and refinement involving teachers and students across multiple educational levels. Quantitative data were analyzed using descriptive statistics (mean and standard deviation) to describe patterns of teacher readiness, student engagement, satisfaction, and module usability. Inferential statistics such as paired sample t-tests were conducted to evaluate differences in learning outcomes before and after the intervention. The findings indicate substantial improvements in teacher digital readiness, student engagement, and learning outcomes. Teachers demonstrated enhanced confidence in integrating mobile-based tools, while students reported increased motivation and autonomy. The resulting framework—the Iterative Contextualized Ubiquitous Learning Framework (ICULF)—offers a replicable model for implementing context-responsive, co-designed digital instruction because it technologically flexible and easily adapted across educational levels. This research contributes both a practical solution for digital pedagogy in high-demand school settings and a theoretical model that redefines the role of educators as instructional designers. The study concludes that effective educational technology integration depends not only on tool quality, but also on participatory, iterative design processes that reflect institutional realities and empower user agency.